Polydioxanone implants: A systematic review on safety and performance in patients. (February 2020) - Martins, Joana A; Lach, Antonina A; Morris, Hayley L; Carr, Andrew J; Mouthuy, Pierre-Alexis
Background: Medical devices made of polydioxanone (a synthetic biodegradable polymer) have been available since the early 1980s. However, no review regarding their performance and safety has been published. Objective: This systematic review intends to review and assess commercially available polydioxanone implants and their safety and performance in patients. Methods: We searched for approved polydioxanone implants in several Food and Drug Administration databases. Then, we performed a literature search for publications and clinical trials where polydioxanone devices were implanted in patients. This search was performed on MEDLINE, Embase, Scopus and other databases. Safety and performance of polydioxanone implants in patients were assessed and compared with the implantation of non-polydioxanone devices, when possible, based on scoring systems developed by the authors that analyse surgical site infection rates, inflammatory reaction rates, foreign body response, postoperative pain and fever. Results: Food and Drug Administration databases search revealed that 48 implants have been approved since 1981, with 1294 adverse reactions or product malfunction in the last decade and 16 recalls. A total of 49 clinical trials and 104 scientific publications were found. Polydioxanone sutures and meshes/plates had low rates of surgical site infection, inflammatory reaction, foreign body response and postoperative fever. Polydioxanone clips/staples reported high rates of surgical site infection, postoperative fever and pain, with sub-optimal clinical performance and poor safety rates. The remaining implants identified showed high levels of safety and performance. Safety scores of polydioxanone implants and non-polydioxanone alternatives are similar. Polydioxanone monofilament sutures perform better than non-polydioxanone alternatives but performance did not differ with remaining polydioxanone implant types. Conclusions: Although polydioxanone clips/staples should be implanted with caution and monitored carefully, in general, safety and performance scores of other polydioxanone implants did not differ from non-polydioxanone alternatives. This review will be a useful reference for researchers and industries developing new polydioxanone medical devices.